Modification of the existing maximum residue levels for pendimethalin in peas (with pods), beans (with pods) and leeks. (15th March 2023) - ,; Bellisai, Giulia; Bernasconi, Giovanni; Brancato, Alba; Cabrera, Luis Carrasco; Castellan, Irene; Del Aguila, Monica; Ferreira, Lucien; Giner Santonja, German; Greco, Luna; Jarrah, Samira; Leuschner, Renata; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant BASF Agro B.V. submitted a request to the competent national authority in France to modify the existing maximum residue levels (MRLs) for the active substance pendimethalin in peas (with pods), beans (with pods) and leeks. The data submitted in support of the request were found to be sufficient to derive MRL proposals for the commodities under assessment. Adequate analytical methods for enforcement are available to control the residues of pendimethalin on the commodities under consideration at the validated LOQ of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of pendimethalin according to the reported agricultural practices is unlikely to present a risk to consumer health.